2019
DOI: 10.1105/tpc.19.00314
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nuclear Ribonucleoprotein H1 Coordinates with Phytochrome and the U1 snRNP Complex to Regulate Alternative Splicing in Physcomitrella patens

Abstract: Plant photoreceptors tightly regulate gene expression to control photomorphogenic responses. Although gene expression is modulated by photoreceptors at various levels, the regulatory mechanism at the pre-mRNA splicing step remains unclear. Alternative splicing, a widespread mechanism in eukaryotes that generates two or more mRNAs from the same pre-mRNA, is largely controlled by splicing regulators, which recruit spliceosomal components to initiate pre-mRNA splicing. The red/ far-red light photoreceptor phytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Post-transcriptionally, phytochromes may control alternative splicing (AS) (extensively reviewed in Cheng et al 114 ). In Physcomitrella patens phytochromes appear to directly regulate AS 115 . In Arabidopsis, despite the identification of a number of splicing factors that can interact with phytochromes 116,117 , it remains debated whether AS is due to direct phytochrome regulation, is an indirect metabolic consequence of de-etiolation or a combination of both 114,118 .…”
Section: New Modes Of Action Of Phytochromesmentioning
confidence: 99%
“…Post-transcriptionally, phytochromes may control alternative splicing (AS) (extensively reviewed in Cheng et al 114 ). In Physcomitrella patens phytochromes appear to directly regulate AS 115 . In Arabidopsis, despite the identification of a number of splicing factors that can interact with phytochromes 116,117 , it remains debated whether AS is due to direct phytochrome regulation, is an indirect metabolic consequence of de-etiolation or a combination of both 114,118 .…”
Section: New Modes Of Action Of Phytochromesmentioning
confidence: 99%
“…AS is a conserved gene regulation in eukaryotes and has been thought to be involved in many biological processes. In recent years the AS regulation in stress has been reported (Laloum et al, 2018;de Francisco Amorim et al, 2018;Calixto et al, 2018;Shih et al, 2019). Here, we found that most DAS genes caused by insect damage were not affected at the transcription level.…”
Section: Discussionmentioning
confidence: 57%
“…A SNP was located in the intron sequence of each RNP1 and SNRNP59. These genes were nuclear ribonucleoprotein, that have mRNA processing function in the plant (Shih et al 2019). Two SNPs were located in the intron of AHL1 gene.…”
Section: Discussionmentioning
confidence: 99%